Nucleos(t)ide withdrawal versus nucleos(t)ide withdrawal with adjuvant pegylated-interferon in HBeAg-negative hepatitis B virus infection (NUC-B trial) - Thursz,M; Lemoine,M; Brown,A; Carey,I; Message,J; Kennedy,P; Forton,D; Wiselka,M; Aldersley,M; Prince,M; McPherson,S; Phillips,S; et al. (Hepatology, 2026)
Background:Finite therapy resulting in sustained hepatitis B surface antigen (HBsAg) loss for patients with chronic HBV infection (CHB) is an important therapeutic goal. In patients with HBeAg-negative infection, nucleos(t)ide analog (NA) withdrawal may achieve HBsAg loss in 5%–20% of patients after 3 years. Pegylated interferon (PEG-IFNα) is a recognized treatment for CHB.Methods:NUC-B was a randomized, multicenter trial in NA-treated non-cirrhotic HBeAg-negative patients with CHB. Patients were allocated to either NA withdrawal alone (control) or NA withdrawal followed by a 16-week course of PEG-IFNα 180 μg weekly commencing 4 weeks after NA cessation (PEG-IFNα). The primary endpoint was HBsAg loss at 3 years.Results:The target recruitment of 240 patients was not achieved. In all, 156 patients, 82 to the control arm, 74 to the PEG-IFNα arm, were recruited between 2017 and 2021; median age 45 years, 24% female, HBV genotypes—A 16%, B 6%, C 4%, D 24%, E 22%, other 1%, nd unknown 26%. At 3 years, 3% of patients in the control arm and 14% of patients in the PEG-IFNα arm lost HBsAg (OR 5.39; 95% CI (1.11, 26.19); p=0.037). In the control arm, 34.9% of patients returned to NA therapy compared with 28.4% in the PEG-IFNα arm. Exaggerated flares occurred in 27.9% of patients in the control arm compared with 13.4% in the PEG-IFNα arm.Conclusions:The use of adjuvant PEG-IFNα therapy after withdrawal of NA therapy increases the rate of HBsAg loss while simultaneously reducing the number of exaggerated flares.